OCT patterns of macular edema and response to bevacizumab therapy in retinal vein occlusion - Höh, Alexandra E.; Ruppenstein, Mira Katharina; Ach, Thomas; Dithmar, Stefan (Graefe's archive for clinical and experimental ophthalmology, 2010)
Baseline OCT morphology of macular edema (ME) due to branch (BRVO) or central retinal vein occlusion (CRVO) was evaluated with respect to response to bevacizumab treatment.